PLASTICITY OF SKELETAL MUSCLE STUDIED BY STEREOLOGY - Eržen, Ida (Image Analysis and Stereology, 2011)
The present contribution provides an overview of stereological methods applied in the skeletal muscle research at the Institute of Anatomy of the Medical Faculty in Ljubljana. Interested in skeletal muscle plasticity we studied three different topics: (i) expression of myosin heavy chain isoforms in slow and fast muscles under experimental conditions, (ii) frequency of satellite cells in young and old human and rat muscles and (iii) capillary supply of rat fast and slow muscles. We analysed the expression of myosin heavy chain isoforms within slow rat soleus and fast extensor digitorum longus muscles after (i) homotopic and heterotopic transplantation of both muscles, (ii) low frequency electrical stimulation of the fast muscle and (iii) transposition of the fast nerve to the slow muscle. The models applied were able to turn the fast muscle into a completely slow muscle, but not vice versa. One of the indicators for the regenerative potential of skeletal muscles is its satellite cell pool. The estimated parameters, number of satellite cells per unit fibre length, corrected to the reference sarcomere length (Nsc/Lfib) and number of satellite cells per number of nuclei (myonuclei and satellite cell nuclei) (Nsc/Nnucl) indicated that the frequency of M-cadherin stained satellite cells declines in healthy old human and rat muscles compared to young muscles. To access differences in capillary densities among slow and fast muscles and slow and fast muscle fibres, we have introduced Slicer and Fakir methods, and tested them on predominantly slow and fast rat muscles. Discussing three different topics that require different approach, the present paper reflects the three decades of the development of stereological methods: 2D analysis by simple point counting in the 70's, the disector in the 80's and virtual spatial probes in the 90's. In all methods the interactive computer assisted approach was utilised.